2005
DOI: 10.1097/01.mlg.0000163339.61909.d0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent SLC26A4 Mutations in Patients with Enlarged Vestibular Aqueduct and/or Mondini Dysplasia: A Unique Spectrum of Mutations in Taiwan, Including a Frequent Founder Mutation

Abstract: The present study disclosed the unique SLC26A4 mutation spectrum in Taiwan, confirmed that IVS7-2A>G arose from a common ancestor, and demonstrated the lack of correlation between genotypes and phenotypes. High prevalence of certain SLC26A4 mutations in East Asians, as revealed here and previously, might largely facilitate mutation screening and genetic counseling in these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 14 publications
7
103
4
Order By: Relevance
“…These molecular and radiological findings indicated that PS and the hearing-loss with EVA fall into one clinical spectrum caused by SLC26A4 mutations, i.e., hearing loss with EVA with/without goiter (Tsukamoto et al 2003). Mutation analysis of SLC26A4 performed in 54 Chinese EVA families (including an area of Mainland China, Taiwan and Singapore) identified 23 different mutations (Yong et al 2001;Dai et al 2005;Wu et al 2005;Yang et al 2005; present study), viz., 14 missense mutations, two nonsense mutations, five intronic nucleotide changes and two deletions (Table 3). Seven of them were found in more …”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…These molecular and radiological findings indicated that PS and the hearing-loss with EVA fall into one clinical spectrum caused by SLC26A4 mutations, i.e., hearing loss with EVA with/without goiter (Tsukamoto et al 2003). Mutation analysis of SLC26A4 performed in 54 Chinese EVA families (including an area of Mainland China, Taiwan and Singapore) identified 23 different mutations (Yong et al 2001;Dai et al 2005;Wu et al 2005;Yang et al 2005; present study), viz., 14 missense mutations, two nonsense mutations, five intronic nucleotide changes and two deletions (Table 3). Seven of them were found in more …”
Section: Discussionsupporting
confidence: 53%
“…Among these recurrent mutations, IVS7-2A>G was reported to be most frequent, and accounted for 69.1% (76/110) of all mutant alleles in the Chinese, suggesting a founder effect of this intronic mutation (Park et al 2003;Wu et al 2005;Yang et al 2005). In the present study, IVS7-2A>G was still the most frequent mutant allele, but accounted for only 22.3% (5/22) of all mutant alleles detected.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…c.919-2AϾG is the most common SLC26A4 mutation associated with EVA among the Han Chinese and Korean populations, with allele frequencies of 0.63 among deaf Chinese with EVA in Taiwan 20 and 0.17 among deaf Koreans with EVA. 19 With no information for EVA, Chinese subjects with SNHL as a group still seem to have the highest c.919-2AϾG MAF among Asian populations: 0.087 in this study compared with 0.022 in Koreans where this variant is considered common, accounting for 36% of SLC26A4 alleles among Korean probands with SNHL in one study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, phenotypes are variable, even with the same mutations. T416P [25], L445W [26], H723R [21,27] and the IVS7-2A>G [28] are involved in either PS or NSHL. Moreover, even intrafamilial phenotypic variability was observed, e.g., the L445W mutation was identified in all affected individuals of a large family, either with PS or with NSHL [26].…”
Section: Slc26a4 (Pds) Deafness Mutationsmentioning
confidence: 99%